2017
DOI: 10.1186/s12986-016-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoids reduce body fat and fat cell size by binding to dietary fat making it less available for absorption in high-fat fed mice

Abstract: BackgroundDietary thylakoids derived from spinach have beneficial effects on body fat accumulation and blood lipids as demonstrated in humans and rodents. Important mechanisms established include delayed fat digestion in the intestine, without causing steatorrhea, and increased fatty acid oxidation in intestinal cells. The objective of our study was to elucidate if increased fecal fat excretion is an important mechanism to normalize adipose tissue metabolism during high-fat feeding in mice supplemented with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It also inhibited liver steatosis in both phases. Prescription of spinach or thylakoid increased PPAR‐ γ gene expression in liver and adipose tissue in previous studies . Activation of PPAR‐ γ by increasing adiponectin circulating levels improved insulin resistance in peripheral tissues such as skeletal muscles and adipose tissue and reduced the transfer of fatty acids to the liver .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It also inhibited liver steatosis in both phases. Prescription of spinach or thylakoid increased PPAR‐ γ gene expression in liver and adipose tissue in previous studies . Activation of PPAR‐ γ by increasing adiponectin circulating levels improved insulin resistance in peripheral tissues such as skeletal muscles and adipose tissue and reduced the transfer of fatty acids to the liver .…”
Section: Discussionmentioning
confidence: 64%
“…In line with our study, Stenkula et al . showed that feeding thylakoids derived from spinach to mice on an HF diet for 2 weeks reduced body weight compared to the control . The intake of thylakoids instead of spinach and the larger sample size ( n = 16) of that study allowed them to observe this effect over a shorter time.…”
Section: Discussionmentioning
confidence: 88%
“…Adding HES to the diet of rats decreased food intake and led to weight loss in the prevention phase; nonetheless, we were not able to make the same observation in the treatment phase. Previous experimental studies have also shown appetite-and weight-reducing properties of HES supplementation at a dose of 200mg/kg and 400mg/kg for 14 days in one study (31), as well as administration of spinach-derived thylakoids for 2 weeks in high-fat fed mice in another (34). Moreover, in a study of overweight women receiving 5 g/d of thylakoid over a period of 12 weeks, body weight decreased (35); on the contrary, in a similar study consisting a dosage of 5.6 g/d administered during eight weeks of intervention, no weight loss was observed (36).…”
Section: Discussionmentioning
confidence: 84%
“…Elevated serum levels of CCK after a thylakoid-rich meal have been reported in several studies (16)(17)(18)(19). In one study, thylakoid intake decreased fat accumulation in the liver by increasing the gene expression of the peroxisome proliferator-activated receptor gamma (PPAR-γ) in adipose tissue (20). Among extracellular matrix proteins, increased gene expression and plasma levels of matrix metalloproteinase 9 (MMP-9) have been observed in alcoholic patients, individuals with viral cirrhosis, and especially NASH (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Stenkula et al observed a considerable reduction in liver fat and fat mass deposits following the consumption of thylakoid‐rich spinach leaf extract for 14 days in high‐fat‐fed mice. They reported that adipocytes isolated from visceral adipose tissue were narrowed, and cell size was also decreased when compared to controls (Stenkula, Stenblom, Montelius, Egecioglu, & Erlanson‐Albertsson, 2017). Albertsson et al reported that the reason behind the use of thylakoid‐containing spinach leaves extract to reduce obesity and body fat is that thylakoids are biological membranes that bind to dietary fats when fats are digested and, then, inhibit pancreatic lipase activity which, ultimately, prevents lipolytic enzymes activity, which is present in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%